An Anonymous Handover Authentication Scheme Based on LTE-A for Vehicular Networks. (3rd July 2018) - Xu, Cheng; Huang, Xiaohong; Ma, Maode; Bao, Hong
Abstract : Vehicular networks play an important role in the intelligent transportation systems which have gained technical supports from car industry. Due to the mobility and the broadcast nature of wireless communication, security of the vehicular networks is a critical issue for the academia and industry. Many solutions have been proposed to target the security provisioning. However, most of them have various shortcomings. Based on the elliptic curve public key cryptography algorithm, in this paper, we propose a new anonymous roaming authentication protocol for the Long Term Evolution-Advanced (LTE-A) supported vehicular networks. For a vehicular LTE-A network, an authentication protocol should be able to fulfill a variety of security requirements, which can be met by our proposal and proved by using Burrows–Abadi–Needham (BAN) logic. Compared with some existing solutions, our scheme has lower communication costs with stronger security functionality. The analyses on the security functions and the performance of the proposed solution show that our scheme is secure and efficient with ability against various types of malicious attacks.